2007
DOI: 10.1371/journal.pone.0000455
|View full text |Cite
|
Sign up to set email alerts
|

Absent or Low Rate of Adult Neurogenesis in the Hippocampus of Bats (Chiroptera)

Abstract: Bats are the only flying mammals and have well developed navigation abilities for 3D-space. Even bats with comparatively small home ranges cover much larger territories than rodents, and long-distance migration by some species is unique among small mammals. Adult proliferation of neurons, i.e., adult neurogenesis, in the dentate gyrus of rodents is thought to play an important role in spatial memory and learning, as indicated by lesion studies and recordings of neurons active during spatial behavior. Assuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
105
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 40 publications
4
105
2
1
Order By: Relevance
“…Long life expectancy and late development of the hippocampal formation however might require other strategies. We have shown that in long living bats hippocampal neurogenesis in adulthood is the exception (Amrein et al, 2007). In other long-living species such as marmoset monkeys, proliferation occurs on a comparatively low level and also decreases with age (Leuner et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Long life expectancy and late development of the hippocampal formation however might require other strategies. We have shown that in long living bats hippocampal neurogenesis in adulthood is the exception (Amrein et al, 2007). In other long-living species such as marmoset monkeys, proliferation occurs on a comparatively low level and also decreases with age (Leuner et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…An earlier study of adult neurogenesis in microchiropterans led to the conclusion that the hippocampus of the species studied had absent to low rates of adult neurogenesis (Amrein et al, 2007). While possible reasons for the absence of adult hippocampal neurogenesis are raised, it appears that no specific conclusion is reached.…”
Section: Introductionmentioning
confidence: 92%
“…While possible reasons for the absence of adult hippocampal neurogenesis are raised, it appears that no specific conclusion is reached. One issue not raised by Amrein et al (2007) was whether the stress of capture/handling of these small mammals may have been an important factor in the lack of adult hippocampal neurogenesis. While Amrein et al (2007) state the the bats were "perfused rapidly after trapping", no estimate of the time that elapsed between trapping and perfusion is provided, thus it is possible that capture stress could pose a serious methodological problem; however, this does not explain the absence of adult hippocampal neurogenesis in the three neotropical bat species obtained from breeding colonies located in Germany, although again, no details regarding handling of these bats prior to perfusion is provided.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations